The Impact of Interactive Science Shows on Student’s Learning Achievement on Fire and Pressure Science Concept for 9th Grader in Brunei - Karim, N.; Roslan, R. (Jurnal Pendidikan IPA Indonesia, 2020)
Informal science learning (ISL) has shown a considerable amount of recognition to the enrichment of science learning. The purpose of this study is to investigate one form of ISL that is on-stage shows also known as science shows to enhance students’ achievement on fire and pressure science concepts and to investigate whether science shows could engage students in science learning. Two science shows were conducted in this study with demonstration characteristics identified as CHAMP merged with the science content development framework for science shows practised by OGDC. In the attempt to identify whether the students learning achievement on fire and pressure science concept were enhanced, experimental design research consisting of a quantitative approach using pretest and posttest achievement tests were utilized. It is followed by BERI protocol to measure the behavioral engagement of students on science show and qualitative approach using structured interviews to elicit students’ insights on the shows. Pretest and posttest scores of the participating students were obtained and analyzed using the Wilcoxon Signed Ranked test. The test revealed a statistically significant increase in scores following participation in the pressure and fire shows, Z= -3.562, p <.001, with a large effect size (r = 0.611) and Z= -3.624, p <.001, with a large effect size (r = 0.622) respectively. Structured interview transcripts (transcribed verbatim) were obtained from six selected students that participated in the experiment whereby two themes were derived, namely; knowledge gained by students and delivery of science show. The statistical and qualitative findings from the study indicated promising evidence that science shows do support students’ achievement on fire and pressure concepts as well as engaging them in learning science.